2016
DOI: 10.1155/2016/5078796
|View full text |Cite
|
Sign up to set email alerts
|

The Power of CRISPR-Cas9-Induced Genome Editing to Speed Up Plant Breeding

Abstract: Genome editing with engineered nucleases enabling site-directed sequence modifications bears a great potential for advanced plant breeding and crop protection. Remarkably, the RNA-guided endonuclease technology (RGEN) based on the clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein 9 (Cas9) is an extremely powerful and easy tool that revolutionizes both basic research and plant breeding. Here, we review the major technical advances and recent applications of the CRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 120 publications
0
15
0
1
Order By: Relevance
“…Therefore, to understand the function of genes and traits in duckweeds, developing tools that can stably and precisely manipulate the gene of interest is critical. To this end, the recently developed CRIPSR/Cas9 system, which was adapted from a naturally occurring genome editing system in bacteria and has been widely used in both animals and plants, is ideal (Cao et al ., ; Ma et al ., ; Yang, ). However, to our knowledge, no study has reported using CRISPR/Cas9 in duckweeds.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, to understand the function of genes and traits in duckweeds, developing tools that can stably and precisely manipulate the gene of interest is critical. To this end, the recently developed CRIPSR/Cas9 system, which was adapted from a naturally occurring genome editing system in bacteria and has been widely used in both animals and plants, is ideal (Cao et al ., ; Ma et al ., ; Yang, ). However, to our knowledge, no study has reported using CRISPR/Cas9 in duckweeds.…”
Section: Introductionmentioning
confidence: 98%
“…The RNA-guided Cas9 nuclease from the bacterial clustered regularly interspaced short palindromic repeats (CRISPR) adaptive immune system provides a powerful and versatile tool for genome engineering of eukaryotic organisms, including plants (Ran, 2013;Bortesi and Fischer, 2015;Cao et al, 2016;Pacher and Puchta, 2016;Puchta, 2017). By simply designing a 20-nt targeting sequence of the guide RNA (Jinek et al, 2012;Cong et al, 2013;Mali et al, 2013), the CRISPR/Cas9 can be targeted to create chromosomal double-stranded breaks (DSBs) at specific sites.…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR/Cas9-mediated targeted gene modification was first introduced for plant genome editing and crop breeding purposes in 2013 1 . This revolutionary technology allows plant breeders to target very specific pieces of DNA without introduction of foreign DNA and to influence key traits accurately and quickly 2 . Although the CRISPR/Cas9 system is an excellent tool for genome editing, the next major challenge is to identify the resulting mutants due to the extent of off-target mutations and the differences in cleavage specificity among species 3 .…”
Section: Introductionmentioning
confidence: 99%